Pemikiran Islam Modern Perspektif Mustafa Kemal - Muhammad Mahfud (FATAWA: Jurnal Pendidikan Agama Islam, 2020)
This paper discusses the perspective of modern Islam, Mustafa Kemal's perspective, especially the reform of Islam in Turkey. The method used in this research is library research using a qualitative approach. The analysis used to analyze the data is content analysis. The results showed that Mustafa Kemal was one of the 19th century qualified Islamic reformers. He has made a huge contribution to changing the mindset of Turkish society. By changing the old traditional order in the Ottoman Empire, and shaping it into a new face with a style of thought that actually does not change "Islam" but only changes the mindset and life order of Muslims to adapt to the demands of the times. Because Islamic values ??can actually be grounded in a country that is in the form of a caliphate, republic and even secular. Even though symbols are also important, what is more important is that the people are able to carry the Islamic substance in every movement of their people's lives. His ideas have brought Turkey to become a developed country that is equal to the international world and at the same time prove that Islamic government is a government in accordance with the demands of the times.